2015
DOI: 10.1074/jbc.m114.592741
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Regulates Nitric Oxide Production in the Kidney Collecting Duct Cells

Abstract: The kidney is an important organ for arterial blood pressure (BP) maintenance. Reduced NO generation in the kidney is associated with hypertension in insulin resistance. NO is a critical regulator of vascular tone; however, whether insulin regulates NO production in the renal inner medullary collecting duct (IMCD), the segment with the greatest enzymatic activity for NO production in kidney, is not clear. Using an NO-sensitive 4-amino-5-methylamino-2',7'-difluorofluorescein (DAF-FM) fluorescent dye, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…Low levels of H 2 O 2 have also been shown to induce NO production. There are reports that NO synthesis is reduced in T2D and hypertension and that insulin regulates NO production [29,30]. We observed that NO level was low in GK rats and ASA treatment increased NO production, which may have stimulated glucose tolerance and increased insulin response.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Low levels of H 2 O 2 have also been shown to induce NO production. There are reports that NO synthesis is reduced in T2D and hypertension and that insulin regulates NO production [29,30]. We observed that NO level was low in GK rats and ASA treatment increased NO production, which may have stimulated glucose tolerance and increased insulin response.…”
Section: Discussionsupporting
confidence: 48%
“…We observed that NO level was low in GK rats and ASA treatment increased NO production, which may have stimulated glucose tolerance and increased insulin response. There are reports that ASA increases NO production in cells and tissues [28] and that NO plays an important role in increasing insulin sensitivity [28,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, hyperinsulinaemia might accelerate the secretion of NO and ET-1 (8,21). In the present study, the results demonstrated that the NO and ET-1 increased significantly from 8 th h of the experiment and reached a peak at 28-32 h (Figs 1 and 2).…”
Section: Discussionsupporting
confidence: 67%
“…These effects occur in parallel to a reduction in glucose uptake and utilization. In the context of renal glomerular hemodynamics, this impairment in insulin metabolic signaling and reduction in PI3K/Akt due to insulin resistance promotes reduced NO production and associated impairment of tubuloglomerular feedback, hyperfiltration, and sodium retention [25,26,27,28,29,30]. Tubuloglomerular feedback is the mechanism by which the kidney autoregulates renal blood flow and glomerular filtration.…”
Section: Mechanisms Of Insulin Resistance and Impact Of Insulin On Thmentioning
confidence: 99%